2010
DOI: 10.1590/s1982-56762010000400001
|View full text |Cite
|
Sign up to set email alerts
|

In vitro production of conidia of Alternaria solani

Abstract: Sporulation of Alternaria solani can be scarce and is often reduced when the fungus is cultivated in vitro. A series of experiments were conducted to assess the effects of moisture, mycelial wounding, light quality and photoperiod, and culture media on conidial production. A procedure to induce sporulation based on mycelial wounding and dehydration was adapted and validated. Best results were obtained when fungal colonies were grown in V8 medium at 25 o C in the dark with agitation for seven days; the mycelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 20 publications
1
14
0
2
Order By: Relevance
“…Conidiogenesis of Alternaria species depends on many environmental and endogenous stimuli, but mainly on available nutrients, photoperiod and temperature (Hubballi et al ., ; Rodrigues et al ., ; Su et al ., ); however, on PDA plates, A. brassicicola sporulates easily in the dark over a wide temperature range. In the present study, conidiogenesis was observed at 48 hpi on all Brassica varieties and, surprisingly, it also occurred at an early stage of the A. brassicicola infection cycle, directly from a mature conidium.…”
Section: Discussionmentioning
confidence: 98%
“…Conidiogenesis of Alternaria species depends on many environmental and endogenous stimuli, but mainly on available nutrients, photoperiod and temperature (Hubballi et al ., ; Rodrigues et al ., ; Su et al ., ); however, on PDA plates, A. brassicicola sporulates easily in the dark over a wide temperature range. In the present study, conidiogenesis was observed at 48 hpi on all Brassica varieties and, surprisingly, it also occurred at an early stage of the A. brassicicola infection cycle, directly from a mature conidium.…”
Section: Discussionmentioning
confidence: 98%
“…PDA and V 8 juice media were prepared based on Rodrigues et al, (2010) protocol while Pradeep et al, (2013) protocol was used for preparation of MEA medium. A volume of 20 ml sterilized medium was poured in each Petri plate and allowed to solidify.…”
Section: Morphological and Cultural Characteristics Of Myceliummentioning
confidence: 99%
“…Leslie and Summerell (2006) have included light as another limiting factor of spore release in Fusarium spp. In addition, culture medium, alternative low-high light, and darkness can facilitate sporulation (Rodrigues et al, 2010). Limited amount of salt (CaCO 3 ) can accelerate spore release in Altarnaria alternate, whereas high concentrations of salt can retard the release (Masangkay et al, 2000), indicating the potential role of chemicals in spore release.…”
mentioning
confidence: 99%